WNT10B variants in split hand/foot malformation: Report of three novel families and review of the literature. Issue 7 (3rd May 2019) - Brunelle, Perrine; Jourdain, Anne‐Sophie; Escande, Fabienne; Martinovic, Jelena; Dupont, Juliette; Busa, Tiffany; Moncla, Anne; Frénois, Frédéric; Stichelbout, Morgane; Manouvrier‐Hanu, Sylvie; Petit, Florence
Abstract: Split‐hand/foot malformation (SHFM) is a genetically heterogeneous congenital limb malformation typically limited to a defect of the central rays of the autopod, presenting as a median cleft of hands and feet. It can be associated with long bone deficiency or included in more complex syndromes. Among the numerous genetic causes, WNT10B homozygous variants have been recently identified in consanguineous families, but remain still rarely described (SHFM6; MIM225300). We report on three novel SHFM families harboring WNT10B variants and review the literature, allowing us to highlight some clinical findings. The feet are more severely affected than the hands and there is a frequent asymmetry without obvious side‐bias. Syndactyly of third–fourth fingers was a frequent finding (62%). Polydactyly, which was classically described in SHFM6, was only present in 27% of patients. No genotype–phenotype correlation is delineated but heterozygous individuals might have mild features of SHFM, suggesting a dose‐effect of the WNT10B loss‐of‐function.